Analysis of Synonymous Codon Usage Bias of Zika Virus and Its Adaption to the Hosts - Wang, Hongju (PLoS One, 2016)
Zika virus (ZIKV) is a mosquito-borne virus (arbovirus) in the family Flaviviridae, and the symptoms caused by ZIKV infection in humans include rash, fever, arthralgia, myalgia, asthenia and conjunctivitis. Codon usage bias analysis can reveal much about the molecular evolution and host adaption of ZIKV. To gain insight into the evolutionary characteristics of ZIKV, we performed a comprehensive analysis on the codon usage pattern in 46 ZIKV strains by calculating the effective number of codons (ENc), codon adaptation index (CAI), relative synonymous codon usage (RSCU), and other indicators. The results indicate that the codon usage bias of ZIKV is relatively low. Several lines of evidence support the hypothesis that translational selection plays a role in shaping the codon usage pattern of ZIKV. The results from a correspondence analysis (CA) indicate that other factors, such as base composition, aromaticity, and hydrophobicity may also be involved in shaping the codon usage pattern of ZIKV. Additionally, the results from a comparative analysis of RSCU between ZIKV and its hosts suggest that ZIKV tends to evolve codon usage patterns that are comparable to those of its hosts. Moreover, selection pressure from Homo sapiens on the ZIKV RSCU patterns was found to be dominant compared with that from Aedes aegypti and Aedes albopictus. Taken together, both natural translational selection and mutation pressure are important for shaping the codon usage pattern of ZIKV. Our findings contribute to understanding the evolution of ZIKV and its adaption to its hosts.